ANALISIS MULTIPLIER EFFECT DAN PEMBANGUNAN BERKELANJUTAN PUSAT INFORMASI WISATA - Denny, Agustinus; ., Liyushiana; Yanti, Dewi (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 2 (2021): Jurnal IPTA (December 2021), 2021)
The existence of the Toba Caldera National Geopark Information Center is an indicator of the seriousness of the government in tapping the potential of Lake Toba with the World-recognized National Geopark approach. Therefore, it is very interesting to explore the impact of the Toba Caldera National Geopark Information Center, especially for the surrounding community. On the one hand, the existence of the Toba Caldera National Geopark Information Center as one of the tourist information centers is a question of whether it is really needed, considering that tourists can now access digital information. Therefore this study seeks to see how the Toba Caldera National Geopark Information Center applies the principle of sustainable development to maintain its existence. This research method is a combination of the quantitative Keynesian Income Multiplier method and interview techniques with the sustainable tourism development approach of the United Nations World Tourism Organization (UNWTO) by combining practical principles. The results obtained show that economically, the Toba Caldera National Geopark Information Center has an encouraging impact on the number 1: 1.26, meaning that for each additional tourist expenditure of IDR 10,000, local income will increase by IDR 12,600. On the other hand, the Toba Caldera National Geopark Information Center has attempted to apply the principles of sustainable tourism development in view of the dimensions of business quality, social sustainability and environmental balance recommended by UNWTO, but improvements are needed for aspects of tourism facilities and activities.